Reading comprehension and predictability effects on sentence processing: an event-related potential study - Tabullo, Ángel Javier (2019)
Fil: Tabullo, Ángel Javier. Consejo Nacional de Investigaciones Científicas y Técnicas. Instituto de Ciencias Humanas, Sociales y Ambientales; Argentina